Celastrol nanoemulsion induces immunogenicity and downregulates PD-L1 to boost abscopal effect in melanoma therapy. (February 2021) - Qiu, Nasha; Liu, Yun; Liu, Qi; Chen, Yanzuo; Shen, Limei; Hu, Mengying; Zhou, Xuefei; Shen, Youqing; Gao, Jianqing; Huang, Leaf
Abstract: Programmed cell death-ligand 1 (PD-L1)-based immune checkpoint blockade therapy using the anti-PD-L1 antibody is effective for a subset of patients with advanced metastatic melanoma but about half of the patients do not respond to the therapy because of the tumor immunosuppressive microenvironment. Immunogenic cell death (ICD) induced by cytotoxins such as doxorubicin (DOX) allows damaged dying tumor cells to release immunostimulatory danger signals to activate dendritic cells (DCs) and T-cells; however, DOX also makes tumor cells upregulate PD-L1 expression and thus deactivate T-cells via the PD-1/PD-L1 pathway. Herein, we show that celastrol (CEL) induced not only strong ICD but also downregulation of PD-L1 expression of tumor cells. Thus, CEL was able to simultaneously activate DCs and T-cells and interrupt the PD-1/PD-L1 pathway between T-cells and tumor cells. In a bilateral tumor model, intratumorally ( i.t. ) injected celastrol nanoemulsion retaining a high tumor CEL concentration activated the immune system efficiently, which inhibited both the treated tumor and the distant untreated tumor in the mice ( i.e., abscopal effect). Thus, this work demonstrates a new and much cost-effective immunotherapy strategy — chemotherapy-induced immunotherapy against melanoma without the need for expensive immune-checkpoint inhibitors.